Making IT governance work in a Sarbanes-Oxley world - Bloem, Jaap (Wiley, 2006)
This book discusses a dilemma common to many corporation’s IT departments--the tension between top-down governance directives and the challenge to get everything properly functioning on a bottom-up basis. Making IT governance work does not simply mean adherence to an ABC of (a) going more deeply into rules, (b) implementing a framework, and (c) registering good results. Neither is this book a guide to frameworks and compliance. Its goal is to describe an entire repertoire of resources that can assist in arriving at better IT governance. Among these resources are CobiT, bottom-up governance principles such as distributed leadership constitute another, and portfolio management.